2019
DOI: 10.1021/acs.jnatprod.8b00791
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from Artemisia argyi: Absolute Configuration and Immunosuppressant Activity

Abstract: A library of extracts from plants used in Chinese Traditional Medicine was screened for inhibition of T lymphocyte proliferation. An ethyl acetate extract from aerial parts of Artemisia argyi showed promising activity and was submitted to HPLC-based activity profiling to track the active compounds. From the most active time window, three guaianolides (1, 2, and 5) and two seco-tanapartholides (3 and 4) were identified and, in a less active time window, five new sesquiterpene lactones (8–11, 17), along with six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…We recently found that an ethyl acetate extract of A. argyi suppressed the in vitro proliferation of human primary T lymphocytes in a concentration-dependent, non-cytotoxic manner (Figure 1) and we also isolated a series of compounds that were responsible for this activity (Reinhardt et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…We recently found that an ethyl acetate extract of A. argyi suppressed the in vitro proliferation of human primary T lymphocytes in a concentration-dependent, non-cytotoxic manner (Figure 1) and we also isolated a series of compounds that were responsible for this activity (Reinhardt et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
“…We previously showed that the A. argyi extract inhibited the proliferation of stimulated human T lymphocytes in vitro, and a series of related guaianolides and seco-guaianolides was found to be responsible for most of the inhibitory effects of the extract (Reinhardt et al, 2019). In the present study, we aimed to further substantiate the rationale for the use of A. argyi as an antiinflammatory herbal drug.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations